Additively Manufactured Urban Multispecies Façades for Building Renovation - Iuliia Larikova; Julia Fleckenstein; Ata Chokhachian; Thomas Auer; Wolfgang Weisser; Kathrin Dörfler (Journal of Facade Design and Engineering, 2022)
This research investigates the potential of additive manufacturing and digital planning tools for the creation of location-specific façade redesigns that can host cavity-dependent animal species and develops methods for their realization. The proposed approach is explored based on a case study of a student dormitory in need of renovation in the urban area of Munich. Based on theoretical knowledge and design experimentations that link the fields of architecture, climate-responsive design, terrestrial ecology, and digital fabrication, a set of design principles for the additive manufacturing of inhabitable ceramic tiles is conceived and transferred into a computational design tool. The conception of single tiles and the overall façade design are developed in terms of their positive climatic impact on both the animal species and humans, their nesting opportunities, their structural feasibility, and their integrability with standard ceramic façade systems. To verify the fabricability of the proposed design, a façade fragment was additively manufactured as a prototype in 1:1 scale. The initial findings presented in this paper provide a glimpse of how emerging digital technologies could provide new ways to expand current habitual architectural planning and fabrication tools, to enable the creation of site-specific solutions, and to bring together human and animal needs.